Imminent Death Donation: Ethical and Practical Policy Considerations. Issue 2 (2018) - Potter, Jordan
Abstract : While the practice of organ donation after cardiac death has long been trending upwards in acceptance and use, it is still a highly controversial and practically inefficient method of organ procurement. One policy that has recently been proposed to try and alleviate some of the ethical and practical concerns with organ donation after cardiac death is the practice of imminent death organ donation. This type of live organ donation comes in patients at the end of their life who have decided to withdraw life-sustaining treatment, but still want to ensure that their organs are donated and not wasted, which isn't always the case with organ donation after cardiac death. This paper then gives some ethical and practical reflections and recommendations regarding the potential implementation of this controversial practice into regular transplant practice and policy.